?rea de cobertura em ambiente de propaga??o modelado com a distribui??o K-? - Antonio, Jamil Ribeiro (2003)
Due to the daily influence of cellular mobile telephony in private life, this work presents one of the most important steps in its planning: the calculation of the coverage area of ??a cell. The whole concept necessary for its realization is presented. For a better understanding of the calculations, two approaches will be considered. The first one assumes that the cell is positioned at the cell's boundary, and is estimated in the form of a circle. The second will consider this mobile positioned anywhere within the area of ??a cell, in which it supposes the shape of a circumference. It will be considered, still in the calculation, the existence of four environments that will represent some possible situations of occurring in a mobile communication. Rice, Rayleigh, and Nakagami are three of them, already publicly known, which will contribute to a comparative analysis with the K-? distribution. The presentation of this distribution, as well as its calculation, will be the contribution of this dissertation, demonstrating that it is possible to perform, through it, the desired calculations for the others mentioned above.